2012
DOI: 10.1371/journal.pone.0051100
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Alignment in Carps: Evidence from the Czech Christmas Fish Market

Abstract: While magnetoreception in birds has been studied intensively, the literature on magnetoreception in bony fish, and particularly in non-migratory fish, is quite scarce. We examined alignment of common carps (Cyprinus carpio) at traditional Christmas sale in the Czech Republic. The sample comprised measurements of the directional bearings in 14,537 individual fish, distributed among 80 large circular plastic tubs, at 25 localities in the Czech Republic, during 817 sampling sessions, on seven subsequent days in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…, Hart et al. ), and as wild boars and warthogs are social animals that forage and rest in groups, MA might serve this function in these species. Antiparallel orientation of pairs can be interpreted as an antipredator strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Hart et al. ), and as wild boars and warthogs are social animals that forage and rest in groups, MA might serve this function in these species. Antiparallel orientation of pairs can be interpreted as an antipredator strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, warthogs would also benefit from a landmarkindependent navigation system, for migration and for facilitated navigation and optimal space use within their home ranges. MA has been proposed as a means to prepare co-ordinated flight responses in herding animals (Begall et al 2008, Hart et al 2012, and as wild boars and warthogs are social animals that forage and rest in groups, MA might serve this function in these species. Antiparallel orientation of pairs can be interpreted as an antipredator strategy.…”
Section: Discussionmentioning
confidence: 99%
“…NNE-SSW deflection of the preferred (landing) axis from the “ideal” N-S axis, observed in Europe is a phenomenon which we encounter also in magnetic alignment of diverse other animal species in diverse behavioural contexts: in the grazing and resting cattle, red deer, and roe deer [5-8], hunting foxes [9] or schooling carps [10]. Interestingly, while the mallards in all countries of the eastern hemisphere preferred a NNE-SSW landing axis, the mallards from western Canada and water birds form southern Botswana, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Directional bearings were measured in 14,537 individuals in 25 different locations. It was found that the C. carpio showed specific preference for alignment in accordance with the lines of the geomagnetic field; i.e ., N–S (Hart et al, ).…”
Section: Behaviour Of Fry and Adult Fishes In Magnetic Fieldsmentioning
confidence: 99%